The Cult of Castor and Pollux in Ancient Rome : Myth, Ritual, and Society - Gartrell, Amber (University of Cambridge ESOL Examinations, 2021)
This book analyses the cult of the Dioscuri and its development, utilising new methodological approaches and a wide range of ancient evidence. This development reveals the significant interactions between Roman religion, politics and society. This book will be of use to scholars and students of ancient religion and history